Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2001
DOI: 10.1097/00004836-200104000-00008
|View full text |Cite
|
Sign up to set email alerts
|

The Exacerbation of Pancreatic Endocrine Dysfunction by Potent Pancreatic Exocrine Supplements in Patients with Chronic Pancreatitis

Abstract: In conclusion, high-dose pancreatin mini-microspheres improved, but did not normalize, fat absorption, possibly because of the residual influence of diabetes and malnutrition on absorptive function. In view of the brittle nature of blood glucose control in malnourished insulin-dependent patients, enzyme adjustment should be carefully supervised in-hospital.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
0
6

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(55 citation statements)
references
References 16 publications
3
46
0
6
Order By: Relevance
“…Improved blood glucose control and reduced glycated haemoglobin, following PERT, has previously been observed [7,9]. However, other studies have observed no effect [10][11][12]. By using young pigs with induced exocrine pancreatic insufficiency, we found that the presence of pancreatic enzymes in the gut lumen resulted in improved direct utilization of blood glucose and improved growth performance, without reinforcing insulin release [3].…”
Section: Introductionsupporting
confidence: 60%
“…Improved blood glucose control and reduced glycated haemoglobin, following PERT, has previously been observed [7,9]. However, other studies have observed no effect [10][11][12]. By using young pigs with induced exocrine pancreatic insufficiency, we found that the presence of pancreatic enzymes in the gut lumen resulted in improved direct utilization of blood glucose and improved growth performance, without reinforcing insulin release [3].…”
Section: Introductionsupporting
confidence: 60%
“…One randomized controlled trial with PES in patients with apancreatic diabetes revealed major difficulties with controlling blood sugars on changing from active enzyme replacement to placebo and vice versa, suggesting that enzyme adjustment should be carefully supervised in a hospital. 16 In another randomized controlled trial of insulin-dependent diabetics with PEI, there were no significant differences in hemoglobin A1C, fasting glucose levels, or 2-hour postprandial glucose levels in patients receiving PES as compared to those not receiving PES. 51 A reduction in mild and moderate hypoglycemia was observed in patients receiving PES and the authors concluded that PES therapy …”
Section: Malnutritionmentioning
confidence: 94%
“…14 Randomized placebo controlled trials have shown that treatment with PES improves steatorrhea, as measured by increased fat absorption, reduced fecal fat excretion, decreased stool weight and frequency, improved stool consistency and improved symptom scores. [15][16][17][18] Other studies have demonstrated that patients receiving PES report weight gain and improved quality of life, and studies demonstrate decreased defecation rates, 19 increased cholesterol absorption and improved enterohepatic cycling of bile salts.…”
Section: Dovepressmentioning
confidence: 99%
“…Another interesting observation was that changing treatment from active enzyme supplementation to placebo [and vice versa] resulted in major problems with glucose control; blood glucose levels became abnormal in 28 of 29 patients, one patient required hospitalization for symptomatic hypoglycaemia during placebo treatment, and one developed diabetic ketoacidosis after recommencing active enzyme supplementation. They came up with the suggestion that enzyme initiation and initial adjustment should be carefully supervised in-hospital [26]. In another small study, enzyme replacement did not result in any positive effect on HbA1c but more stable control was observed over the entire day on pancreatic supplementation [27].…”
Section: Therapeutic Implicationsmentioning
confidence: 99%